2020
DOI: 10.1109/access.2020.2969812
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Land Use/Land Cover Extraction From High-Resolution Satellite Images Based on Adaptive Context Inference

Abstract: In this paper, automatic extraction of multi-context and multi-scale land use/land cover vegetation from high-resolution remote sensing images is tackled, aiming to solve typical challenges in classifying remote sensing images at a pixel level. To solve small inter-class differences and large intraclass differences between the vegetation and background, we introduce a vegetation-feature-sensitive focus perception (FP) module. Considering the intrinsic properties of vegetation objects, we established an adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Automated land cover mapping is an active field of research with many machine learning approaches suggested, solving tasks such as vegetation extraction [9] or land cover change detection [10]. In creating a global land cover map, CORINE [11] uses several data fusion and pre-processing steps together with ancillary data sources to generate a training dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Automated land cover mapping is an active field of research with many machine learning approaches suggested, solving tasks such as vegetation extraction [9] or land cover change detection [10]. In creating a global land cover map, CORINE [11] uses several data fusion and pre-processing steps together with ancillary data sources to generate a training dataset.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, the rapid advancements in space optical remote sensing technology have greatly promoted the Earth Observation System [15] and it has emerged as a potent and impactful tool for acquiring regional and global vegetation information [16][17][18][19]. Currently, a variety of optical, hyperspectral, and radar remote sensing data have been widely utilized for vegetation extraction, such as Gaofen and ZY series data [20][21][22] from China, Sentinel series data from the European Space Agency [23][24][25], and Landsat series data from the United States [26]. For applying remote sensing technology to urban vegetation research, a critical aspect is to extract ground truth vegetation information from images swiftly and effectively.…”
Section: Introductionmentioning
confidence: 99%
“…In remote sensing object recognition, [4], [5], and [6] use DeepLab [7] [8]. Fully Convolutional Networks (FCNs) [9] are used in [10], [11], and [12].…”
Section: Introductionmentioning
confidence: 99%